Old site, new problems: the Gravettian campsite of Doroshivtsi III, Middle Dniester River Valley, western Ukraine. (August 2022) - Połtowicz-Bobak, Marta; Kulakovska, Larissa; Bobak, Dariusz; Usik, Vitaly; Kononenko, Olesia; Łanczont, Maria; Mroczek, Przemysław; Standzikowski, Karol; Demay, Laëtitia; Nadachowski, Adam; Lemanik, Anna
Abstract: Abstract : New research at the Doroshivtsi site in Ukraine has provided data that allow fresh insights into a well-known and important Gravettian site in the Middle Dniester Valley.